Single-cell RNA sequencing to dissect the immunological network of liver fibrosis in Schistosoma japonicum-infected mice - Zhang, Yu; Li, Junhui; Li, Hao; Jiang, Jie; Guo, Chen; Zhou, Chen; Zhou, Zhaoqin; Ming, Yingzi (Frontiers in Immunology, 2022)
Liver fibrosis is a poor outcome of patients with schistosomiasis, impacting the quality of life and even survival. Eggs deposited in the liver were the main pathogenic factors of hepatic fibrosis in Schistosomiasis japonica. However, the mechanism of hepatic fibrosis in schistosomiasis remains not well defined and there is no effective measure to prevent and treat schistosome-induced hepatic fibrosis. In this study, we applied single-cell sequencing to primarily explore the mechanism of hepatic fibrosis in murine schistosomiasis japonica(n=1) and normal mouse was served as control(n=1). A total of 10,403 cells were included in our analysis and grouped into 18 major cell clusters. Th2 cells and NKT cells were obviously increased and there was a close communication between NKT cells and FASLG signaling pathway. Flow cytometry analysis indicated that the expression of Fasl in NKT cells, CD8+ T cell and NK cell were higher in SJ groups. Arg1, Retnla and Chil3, marker genes of alternatively activated macrophages (M2), were mainly expressed in mononuclear phagocyte(1) (MP(1)), suggesting that Kupffer cells might undergo M2-like polarization in fibrotic liver of schistosomiasis. CXCL and CCL signaling pathway analysis with CellChat showed that Cxcl16-Cxcr6, Ccl6-Ccr2 and Ccl5-Ccr5 were the most dominant L−R and there were close interactions between T cells and MPs. Overall, our research profiled a preliminary immunological network of hepatic fibrosis in murine schistosomiasis japonica, which might contribute to a better understanding of the mechanisms of liver fibrosis in schistosomiasis. NKT cells and CXCL and CCL signaling pathway such as Cxcl16-Cxcr6, Ccl6-Ccr2 and Ccl5-Ccr5 might be potential targets to alleviate hepatic fibrosis of schistosomiasis.